Quaternary ammonium salt-oligomeric lactic acid double-graft polymerized rosin / polylactic acid antibacterial fiber and preparation method thereof

By grafting quaternary ammonium cations and oligomeric lactic acid segments in PLA fibers, the antibacterial and tensile properties of PLA/PR composites are improved, the shortcomings of existing materials are solved, and high-efficiency antibacterial and high-tough fiber materials are achieved, suitable for medical fibers and functional textiles.

CN120554802AActive Publication Date: 2025-08-29JIANGNAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510696947.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-28
Publication Date
2025-08-29
Estimated Expiration
2045-05-28

AI Technical Summary

Technical Problem

PLA/PR composites have problems such as insufficient antibacterial effect and poor tensile resistance. It is necessary to provide a PLA/PR composite with high antibacterial properties and high tensile resistance.

Method used

The quaternary ammonium salt cation and oligolactic acid segment were grafted onto the polymerized rosin framework by chemical grafting method, and PLA/PR-g-OLA10-N+ masterbatch was prepared. The synergistic effect of modified rosin improved the tough structure of PLA fibers and imparted high-efficiency antibacterial properties to the material.

Benefits of technology

The prepared composite modified fibers achieved excellent antibacterial and mechanical properties improvements under the addition of a small amount of modified rosin. The fiber breaking strength was reduced by about 15%, but the elongation rate of break was increased by 23%, and the antibacterial rate of E. coli and Staphylococcus aureus reached 99% and 93.6%, which broadened the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120554802A_ABST
    Figure CN120554802A_ABST
Patent Text Reader

Abstract

The invention discloses a quaternary ammonium salt-oligomeric lactic acid double-graft polymerized rosin / polylactic acid antibacterial fiber and a preparation method thereof, and belongs to the technical field of high polymer materials and modified fibers. According to the method, quaternary ammonium salt and oligomeric lactic acid are successfully grafted to polymerized rosin through a chemical grafting method, a polymerized rosin-based quaternary ammonium salt antibacterial agent is prepared, and PLA / PR-g-OLA (10-N +) antibacterial fibers are prepared through a melt spinning technology. The preparation method disclosed by the invention is simple, environment-friendly in process and high in controllability, provides a new strategy for preparing the functional PLA fiber with efficient antibacterial property and controllable mechanical property by a melt spinning method, and shows potential application value in the fields of medical dressings, antibacterial packaging and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials and modified fibers, and in particular to a quaternary ammonium salt-oligolactic acid double-grafted polymerized rosin / polylactic acid antibacterial fiber and a preparation method thereof. Background Art

[0002] With the increasing attention paid to environmental protection and sustainable development, the research and development of biodegradable materials has gradually become a research hotspot in the field of modern materials science. Polylactic acid (PLA) is a bio-based degradable polymer derived from renewable resources. Due to its green and environmentally friendly characteristics, it has attracted much attention in the field of fiber materials, especially in medical dressings, antibacterial packaging and other scenarios, showing broad prospects. However, the inherent limitations of PLA, such as high brittleness, easy degradation during thermal processing, and lack of antibacterial activity, have seriously restricted its application in high value-added fields. Therefore, the development of an antibacterial polylactic acid fiber with excellent antibacterial properties, good mechanical properties and a simple preparation process has become an urgent problem to be solved.

[0003] To overcome these limitations, researchers have begun exploring ways to improve the performance of polylactic acid (PLA) through composite modification. Polymerized rosin (PR) has garnered widespread attention in the field of biodegradable materials due to its excellent processability, natural properties, and certain antibacterial properties. The addition of polymerized rosin not only enhances the thermoplasticity and processing fluidity of PLA, but also improves its surface properties and antibacterial properties. However, unmodified PR has poor compatibility with PLA, and direct addition of PR results in a decrease in the mechanical properties of PLA fibers. Furthermore, the antibacterial capacity of unmodified PR is limited, leaving much room for improvement. Summary of the Invention

[0004] Technical issues

[0005] PLA / PR composite materials face problems such as insufficient antibacterial effect and poor tensile strength. Therefore, it is necessary to provide a method for preparing PLA / PR composite materials with high antibacterial and high tensile strength.

[0006] Technical content

[0007] The object of the present invention is to provide a PLA / PR-g-OLA 10 -N + Composite modified fiber and preparation method thereof, quaternary ammonium salt cation (N + ) and oligolactic acid segments were successfully grafted onto a polymerized rosin (PR) backbone. The synergistic effect of the modified rosin during melt spinning improved the toughness and structure of PLA fibers, imparting them with highly effective antibacterial properties. The resulting composite modified fibers meet the requirements of high-performance textile materials, particularly those in medical fibers and functional textiles, and possess significant practical application value and market prospects.

[0008] The technical solution adopted by the present invention to solve its technical problem is:

[0009] A PLA / PR-g-OLA 10 -N + Masterbatch, the PLA / PR-g-OLA 10 -N + The masterbatch is composed of the following components in percentage by mass:

[0010] Polylactic acid: 95-98%,

[0011] Antibacterial double-grafted polymerized rosin: 2-5%.

[0012] Furthermore, the preparation process of the antibacterial double-grafted polymerized rosin is as follows:

[0013] (1) Dissolving polymerized rosin in ethanol, adding maleic anhydride, reacting under ultraviolet irradiation, then adding acetic acid for precipitation, and then filtering to obtain product 1;

[0014] (2) dissolving product 1 in ethanol, adding 3-dimethylaminopropylamine, cooling and crystallizing to obtain product 2;

[0015] (3) Lactide is melted, stannous octoate is added, reacted, and then dissolved in dichloromethane to obtain reaction solution 1;

[0016] (4) Product 2 was dissolved in dichloromethane, DMAP and DCC were added, and then added to reaction solution 1 for reaction, followed by rotary evaporation and filtration to obtain product 3;

[0017] (5) The product 3 was dissolved in THF and heated to 50-70°C, ethyl bromide was added for reaction, and then filtered and dried to obtain the antibacterial double-grafted polymerized rosin.

[0018] Furthermore, in step (1), the ratio of the mass of polymerized rosin to the volume of ethanol is 1 g:5-10 mL.

[0019] Furthermore, in step (1), the mass ratio of polymerized rosin to maleic anhydride is 1:0.2-0.5.

[0020] Furthermore, in step (1), the ultraviolet irradiation is performed using a 254 nm, 30 W ultraviolet lamp.

[0021] Furthermore, the reaction in step (1) is carried out at 20-25° C. for 2-5 h.

[0022] Furthermore, in step (2), the ratio of the mass of product 1 to the volume of ethanol is 1 g:5-10 mL.

[0023] Furthermore, in step (2), the mass ratio of product 1 to 3-dimethylaminopropylamine is 1:0.1-0.5.

[0024] Furthermore, the reaction in step (2) is carried out at 80-90° C. for 2-5 h.

[0025] Furthermore, in step (3), the mass ratio of lactide to stannous octoate is 75:0.1-0.5.

[0026] Furthermore, the reaction in step (3) is carried out at 80-90° C. for 2-5 h.

[0027] Furthermore, in step (3), the ratio of the mass of lactide to the volume of dichloromethane is 1 g:5-10 mL.

[0028] Furthermore, in step (4), the ratio of the mass of product 2 to the volume of dichloromethane is 1 g:5-10 mL.

[0029] Furthermore, in step (4), the mass ratio of product 2 to DMAP is 1:0.01-0.05.

[0030] Furthermore, in step (4), the mass ratio of product 2 to DCC is 1:0.1-0.5.

[0031] Furthermore, in step (4), the ratio of the mass of the product 2 to the volume of the reaction solution 1 is 1 g:15-25 mL.

[0032] Furthermore, the reaction in step (4) is carried out at 20-25° C. for 5-10 hours.

[0033] Furthermore, in step (5), the ratio of the mass of product 3 to the volume of THF is 1 g:2-5 mL.

[0034] Furthermore, in step (5), the mass ratio of product 3 to bromoethane is 1:0.1-0.5.

[0035] Furthermore, the reaction time in step (5) is 20 to 40 hours.

[0036] Furthermore, the polylactic acid is thermoplastic polylactic acid with a melting point of 175°C.

[0037] Furthermore, the relative molecular mass of the polylactic acid is 1 to 2×10 5 , its melt index is 4-5g / 10min.

[0038] Furthermore, the softening point of the polymerized rosin is 130-140°C.

[0039] Furthermore, the relative molecular weight of the polymerized rosin is 600-1000, and its melt index is 20-80 g / 10 min.

[0040] PLA / PR-g-OLA provided by the present invention 10 -N + The application of masterbatch in the textile field and environmental protection material field.

[0041] Further, the application in the textile field includes the use of PLA / PR-g-OLA 10 -N + Masterbatch to prepare fiber.

[0042] Furthermore, the application of the environmentally friendly material field includes the use of PLA / PR-g-OLA 10 -N + Masterbatch preparation for film preparation.

[0043] A PLA / PR-g-OLA 10 -N + The preparation method of the masterbatch comprises the following steps:

[0044] (1) grinding PLA to obtain PLA powder;

[0045] (2) grinding the antibacterial double-grafted polymerized rosin to obtain antibacterial double-grafted polymerized rosin powder;

[0046] (3) PLA powder and antibacterial double-grafted polymerized rosin powder are dried to remove moisture, and then the dried powders are blended and melt-blended and extruded using a twin-screw extruder. After melt drawing and cooling, the powders are pelletized to obtain masterbatches.

[0047] As an embodiment of the present invention, in step (1), the particle size of the PLA powder is controlled to be 20-50 mesh; theoretically, the smaller the particle size, the better; however, in actual operation, due to the large amount of heat generated during the mechanical grinding process, grinding the PLA too finely may cause thermal degradation of some PLA.

[0048] Furthermore, the amount of polylactic acid added in step (1) is PLA / PR-g-OLA 10 -N + 95-98wt% of the masterbatch mass.

[0049] Furthermore, the amount of modified polymerized rosin added in step (1) is PLA / PR-g-OLA 10 -N + 2-5wt% of the masterbatch mass.

[0050] Furthermore, the drying condition in step (1) is drying at 60±5°C for 12±5h.

[0051] Furthermore, the temperature of each zone of the twin-screw extruder described in step (3) is 175° C. to 185° C., and the screw speed is 20-30 r / min.

[0052] A PLA / PR-g-OLA 10 -N + Composite modified fiber, the composite modified fiber is composed of PLA / PR-g-OLA 10 -N + The masterbatch is made by melt spinning.

[0053] As an embodiment of the present invention, the temperature of each zone of the melt spinning is 175° C. to 185° C., and the drawing speed is 800 r / min to 1000 r / min.

[0054] As an embodiment of the present invention, the spinning temperature in the melt spinning is 60-65° C. and the spinning time is 5-10 minutes.

[0055] PLA / PR-g-OLA provided by the present invention 10 -N + The application of composite modified fibers in the production of protective clothing, antibacterial medical supplies or biodegradable materials.

[0056] Beneficial effects of the present invention:

[0057] (1) Simple preparation: The present invention adopts a melt grafting blending spinning preparation method, and the entire process is simple to operate and has a short process flow. It does not require complex equipment and tedious steps, which reduces production costs and strict requirements on the operating environment, making the production process more efficient and controllable, facilitating large-scale industrial production, and significantly improving production efficiency and economic benefits.

[0058] (2) Environmentally friendly raw materials: Polylactic acid (PLA) is used as the base resin, which is derived from natural starch raw materials such as corn and wheat. It is biodegradable and will not cause environmental pollution. At the same time, the quaternary ammonium salt-oligolactic acid grafted polymer rosin used is also made by chemical grafting based on renewable resources. The raw materials are renewable, non-toxic and harmless, which meets the urgent demand of modern society for environmentally friendly materials, is friendly to the ecological environment, reduces the burden of traditional non-degradable materials on the environment, and contributes to sustainable development.

[0059] (3) Excellent effect: The composite modified fiber has excellent antibacterial properties. When the modified rosin addition amount is 5wt%, the quaternary ammonium salt cations are evenly distributed on the fiber surface, and the antibacterial rates against Escherichia coli and Staphylococcus aureus are both over 99%. In addition, mechanical property tests show that the addition of 2wt% modified polymerized rosin can reduce the fiber breaking strength by about 15% compared with pure PLA, but significantly increase the elongation at break by 23%, and effectively improve the toughness of the material. At the same time, the antibacterial rates against Escherichia coli and Staphylococcus aureus reach 95% and 93.6%, respectively. The above results show that the polylactic acid composite fiber of the present invention can achieve excellent comprehensive performance with the addition of a small amount of modified rosin (2-5wt%), broadening the application range of polylactic acid fiber in multiple fields such as textiles, medical supplies, and personal protective equipment, and meeting the demand for high-performance environmentally friendly fibers in different scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is the synthesis diagram of antibacterial double-grafted polymerized rosin.

[0061] Figure 2 The figures are the mechanical property test results of the embodiments and comparative examples.

[0062] Figure 3 The antibacterial performance test results of the embodiments and comparative examples are shown in FIG. DETAILED DESCRIPTION

[0063] The following describes preferred embodiments of the present invention. It should be understood that the embodiments are for better explanation of the present invention and are not intended to limit the present invention.

[0064] The polylactic acid (PLA) used in this invention was purchased from Anhui Fengyuan Futailai Polylactic Acid Co., Ltd., and the product name is polylactic acid particles FY801; the specification is for industrial use. Polymerized rosin (PR) was purchased from Shenzhen Jitian Chemical Co., Ltd., with a softening point of 135-145°C and an acid value of 140 mgKOH / g. Lactide, maleic anhydride (AR grade), dichloromethane (DCM, 99.9%), tetrahydrofuran (THF, 99.5%), stannous octoate (95%), 3-dimethylaminopropylamine (99.7%), 4-dimethylaminopyridine (DAMP, 99%), and N,N'-dicyclohexylcarbodiimide (DCC, 99%) were all purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; nutrient broth and nutrient agar were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0065] The following modified polymerized rosin (PR-g-OLA 10 -N + ) is prepared by:

[0066] (1) Polymerized rosin (40 g) was dissolved in ethanol (250 mL), and maleic anhydride (15 g) was added. The mixture was reacted at 20-25°C for 3 h under ultraviolet light (254 nm, 30 W). Acetic acid (100 mL) was then added to precipitate crystals. The crude product MT1 was filtered and purified by crystallization from acetic acid twice to obtain MT1.

[0067] (2) MT1 (35 g) was dissolved in ethanol (250 mL), and 3-dimethylaminopropylamine (10 mL) was added. The mixture was reacted at 85°C for 3 h, and then cooled and crystallized to obtain MT2.

[0068] (3) Lactide (75 g) was melted at 160°C, stannous octoate (0.2 g) was added, and the mixture was reacted at 85°C for 3 h. The mixture was dissolved in DCM (500 mL) to obtain reaction solution 1 for later use. The reaction system was anhydrous and protected by argon.

[0069] (4) MT2 (25 g) was dissolved in DCM (250 mL), and DMAP (0.5 g) and DCC (5 g) were added to the reaction solution 1. The mixture was reacted at 20-25°C for 6 h. The solvent was removed by rotary evaporation, and the crude product of MT3 was obtained by filtration. The crystals were washed twice with ethanol to obtain pure MT3.

[0070] (5) MT3 (95 g) was dissolved in THF (250 mL) and gradually heated to 60°C until a clear and uniform solution was obtained. 10 mL of bromoethane was then added dropwise to the solution and allowed to react for 24 hours. During this period, MT4 was continuously precipitated, which was then collected and washed three times with THF and dried at 60°C to obtain the finished MT4, i.e., modified polymerized rosin (PR-g-OLA). 10 -N + ).

[0071] Example 1

[0072] Raw material: PLA30g

[0073] Preparation process: PLA is ground into powder, dried, and then melt-blended and extruded through a twin-screw extruder. After melt drawing and air cooling, the powder is pelletized to produce PLA masterbatch. The temperatures of zones 1 to 6 of the twin-screw extruder are 180°C, 185°C, 185°C, 185°C, 175°C, and 170°C, respectively, and the screw speed is controlled at 60-75r / min.

[0074] Then, the PLA masterbatch is spun through a melt spinning machine to obtain a fiber product; the temperatures of the melt spinning machine are: 175°C for the upper cavity plate, 180°C for the lower cavity plate, the spinning drafting speed is 1000r / min~1200r / min; the spinning setting temperature is 60~65°C, and the time is 5-10min.

[0075] Example 2

[0076] The difference from Example 1 is the selection of raw materials, which are PLA 29.85g, PR-g-OLA 10 -N + 0.15g.

[0077] Example 3

[0078] The difference from Example 1 is the selection of raw materials, which are PLA 29.7g, PR-g-OLA 10 -N + 0.3g.

[0079] Example 4

[0080] The difference from Example 1 is the selection of raw materials, which are PLA 29.4g, PR-g-OLA 10 -N + 0.6g.

[0081] Example 5

[0082] The difference from Example 1 is the selection of raw materials, which are PLA 29.1g, PR-g-OLA 10 -N + 0.9g.

[0083] Example 6

[0084] The difference from Example 1 is the selection of raw materials, which are PLA 28.8g, PR-g-OLA 10 -N + 1.2g.

[0085] Example 7

[0086] The difference from Example 1 is the selection of raw materials, which are PLA 28.5g, PR-g-OLA 10 -N + 1.5g.

[0087] Comparative Example 1

[0088] The difference from Example 7 is the selection of raw materials, which are PLA 28.5g, PR-gN + 1.5g;

[0089] Among them PR-gN + The preparation process is:

[0090] (1) Polymerized rosin (40 g) was dissolved in ethanol (250 mL), and maleic anhydride (15 g) was added. The mixture was reacted at 20-25°C for 3 h under ultraviolet light (254 nm, 30 W). Acetic acid (100 mL) was then added to precipitate crystals. The crude product MT1 was filtered and purified by crystallization from acetic acid twice to obtain MT1.

[0091] (2) MT1 (35 g) was dissolved in ethanol (250 mL), and 3-dimethylaminopropylamine (10 mL) was added. After reacting at 85 °C for 3 h, PR-gN was obtained by cooling and crystallization. + .

[0092] Comparative Example 2

[0093] The difference from Comparative Example 1 is the selection of raw materials, which is 28.5g of PLA and 1.5g of PR.

[0094] The raw material ratios and compositions in each embodiment are summarized as shown in Table 1.

[0095] Table 1 Summary of original proportions in the examples (unit: g)

[0096]

[0097] The mechanical properties of the above examples were tested, and the test results are shown in Figure 1 And Table 2. The test method refers to GB / T14337 "Test method for tensile properties of chemical fiber filaments".

[0098] Table 2 Mechanical properties test results of the examples

[0099] Breaking strength (cN / dtex) Elongation at break (%) Example 1 2.19 35.4 Example 2 1.31 54.8 Example 3 1.32 55.4 Example 4 1.87 43.6 Example 5 1.42 49.2 Example 6 1.59 48.5 Example 7 1.66 44.5 Comparative Example 1 1.56 40.6 Comparative Example 2 1.41 38.84

[0100] from Figure 1As shown in Table 2, with the introduction of modified polymeric rosin, the fiber's overall breaking strength shows a downward trend, while its elongation at break shows an upward trend. This is primarily due to the good compatibility of the oligolactic acid segments with the PLA matrix. The flexible segments are embedded in the PLA molecular network, plasticizing the PLA matrix and reducing the segment slip resistance, thereby reducing the fiber's ability to resist external tensile stress, manifesting as a decrease in breaking strength. Conversely, the introduction of the flexible segments imparts greater segment mobility to the PLA matrix, allowing the molecular chains to reorient themselves along the direction of the external force during stretching, resulting in plastic deformation rather than brittle fracture, thus improving the elongation at break. When the modified polymeric rosin addition level is 2 wt%, the breaking strength decreases by approximately 15% compared to pure PLA fiber, while the elongation at break increases by 23%, significantly enhancing toughness. As the amount of modified polymeric rosin continues to increase, the breaking strength decreases slightly, but still generally meets the basic requirements for weaving. The mechanical properties of Comparative Examples 1 and 2 are inferior to those of the examples.

[0101] The above examples were tested for antibacterial properties, and the test results are shown in Table 3. The test method was based on GB / T 20944.2-2008 "Evaluation of antibacterial properties of textiles - Part 3: Oscillation method".

[0102] Table 3 Antibacterial performance test results of the embodiments and comparative examples

[0103]

[0104] As can be seen from the data in Table 3, Example 1 exhibited antibacterial rates of 47.6% and 59.2% against Escherichia coli and Staphylococcus aureus, respectively, indicating that the antibacterial properties of pure PLA fiber are relatively limited. Quaternary ammonium salts significantly inhibited the bacterial activity of both bacteria, and higher concentrations of antibacterial double-grafted polymerized rosin further enhanced the inhibitory effect. The blended fiber began to exhibit excellent antibacterial properties when the addition amount was increased to 2wt%, and at a doping concentration of 5wt%, the antibacterial rates against Escherichia coli and Staphylococcus aureus reached 99% and 99.99%. Comparative Example 1, in which polymerized rosin was grafted with only quaternary ammonium salts, exhibited only 74% and 78% antibacterial rates against Escherichia coli and Staphylococcus aureus, respectively. This may be due to the lack of oligolactic acid, resulting in poor compatibility between PLA and PR, and the agglomeration of quaternary ammonium salt cations. Comparative Example 2, in which modified polymerized rosin was used, had no antibacterial effect.

[0105] In summary, the present invention provides a new strategy for double grafting of polymerized rosin and a new type of PLA / PR-g-OLA 10 -N +The composite modified fiber and its preparation method, through the rational design of the composite system and optimized formulation, successfully address the problems of existing antimicrobial fiber materials, such as poor mechanical properties and insufficient antimicrobial efficacy. This composite fiber exhibits significant advantages in antimicrobial performance, mechanical properties, and thermal stability, and features a simple preparation process, indicating promising market application potential. This invention not only possesses significant technological innovation but also has broad commercial prospects, positively impacting the textile industry, particularly in the field of antimicrobial materials.

[0106] The embodiments provided above are not intended to limit the scope of the present invention, nor are the steps described to limit their execution order. Any obvious improvements to the present invention made by those skilled in the art in combination with existing common knowledge shall fall within the scope of protection defined by the claims of the present invention.

Claims

1. A PLA / PR-g-OLA 10 -N + The masterbatch is characterized in that PLA / PR-g-OLA 10 -N + The masterbatch is composed of the following components in percentage by mass: composition: Polylactic acid: 95-98%, Antibacterial double-grafted polymerized rosin: 2-5%; The preparation process of the antibacterial double-grafted polymerized rosin is as follows: (1) Dissolving polymerized rosin in ethanol, adding maleic anhydride, reacting under ultraviolet irradiation, then adding acetic acid for precipitation, and filtering to obtain product 1; the mass ratio of polymerized rosin to maleic anhydride is 1:0.2-0.5; (2) dissolving the product 1 in ethanol, adding 3-dimethylaminopropylamine, reacting at 80-90° C. for 2-5 hours, and cooling to crystallize to obtain the product 2; the mass ratio of the product 1 to the 3-dimethylaminopropylamine is 1:0.1-0.5; (3) Melt lactide, add stannous octoate, react at 80-90°C for 2-5 hours, and then dissolve in dichloromethane to obtain reaction solution 1; the mass ratio of lactide to stannous octoate is 75:0.1-0.5; the mass ratio of lactide to dichloromethane is 1 g:5-10 mL (4) Product 2 was dissolved in dichloromethane, DMAP and DCC were added, and then reaction solution 1 was added to react, followed by rotary evaporation and filtration to obtain product 3; the mass ratio of product 2 to DMAP was 1:0.01-0.05; the mass ratio of product 2 to DCC was 1:0.1-0.5; the mass ratio of product 2 to the volume of reaction solution 1 was 1 g:15-25 mL; (5) The product 3 is dissolved in THF and heated to 50-70°C, ethyl bromide is added and reacted for 20-40 hours, and then filtered and dried to obtain the antibacterial double-grafted polymerized rosin; the mass ratio of the product 3 to ethyl bromide is 1:0.1-0.

5.

2. PLA / PR-g-OLA according to claim 1 10 -N + The masterbatch is characterized in that In step (1), the ratio of the mass of the polymerized rosin to the volume of ethanol is 1 g: 5 to 10 mL; and in step (2), the ratio of the mass of the product 1 to the volume of ethanol is 1 g: 5 to 10 mL.

3. PLA / PR-g-OLA according to claim 1 10 -N + The masterbatch is characterized in that The ratio of the mass of the product 2 in step (4) to the volume of dichloromethane is 1 g:5-10 mL; the ratio of the mass of the product 3 in step (5) to the volume of THF is 1 g:2-5 mL.

4. PLA / PR-g-OLA according to any one of claims 1 to 3 10 -N + The application of masterbatch in the textile field and environmental protection material field.

5. A PLA / PR-g-OLA according to any one of claims 1 to 3 10 -N + The method for preparing a masterbatch is characterized in that: The following steps are involved: (1) grinding PLA to obtain PLA powder; (2) grinding the antibacterial double-grafted polymerized rosin to obtain antibacterial double-grafted polymerized rosin powder; (3) PLA powder and antibacterial double-grafted polymerized rosin powder are dried, and then the dried powders are blended and then melt-blended and extruded using a twin-screw extruder. After melt drawing and cooling, the powders are pelletized to obtain master batches.

6. The preparation method according to claim 5, characterized in that In step (1), the particle size of the PLA powder is 20 mesh to 50 mesh.

7. The preparation method according to claim 5, characterized in that The temperature of each zone of the twin-screw extruder described in step (3) is 175° C. to 185° C., and the screw speed is 20-30 r / min.

8. A PLA / PR-g-OLA 10 -N + The composite modified fiber is characterized in that: The composite modified fiber is made of the PLA / PR-g-OLA according to any one of claims 1 to 3. 10 -N + The masterbatch is made by melt spinning.

9. PLA / PR-g-OLA according to claim 8 10 -N + The composite modified fiber is characterized in that: The temperature of each zone of melt spinning is 175° C. to 185° C., and the drawing speed is 800 r / min to 1000 r / min.

10. PLA / PR-g-OLA according to claim 8 10 -N + The composite modified fiber is characterized in that: The spinning temperature in melt spinning is 60-65°C and the time is 5-10 minutes.

Citation Information

Patent Citations

  • Modified polylactic acid sheet as well as preparation method and application thereof

    CN118931132A

  • Polylactic acid-based resin composition, production method and molded article thereof

    JP2007269915A

  • Antibacterial modified plastic

    WO2022022544A1